Exploring Health Professionals' Experiences With a Virtual Learning and Mentoring Program (Project ECHO) on Pediatric Palliative Care in South Asia. (August 2021) - Doherty, Megan; Modanloo, Shokoufeh; Evans, Emily; Rowe, Jennifer; Newhook, Dennis; Palat, Gayatri; Archibald, Douglas
Project ECHO (Extension of Community Healthcare Outcomes) is an innovative model of online education which has been proposed to enhance access to palliative care in resource-limited settings. There is limited literature describing how health care providers in low-and middle-income countries benefit from and learn from this type of training. This qualitative description study explores the learning experiences of participants in a Project ECHO program on pediatric palliative care in South Asia through focus group discussions. Discussions were transcribed, coded, independently verified, and arranged into overarching themes. We identified learning themes including the importance of creating a supportive learning community; the opportunity to share ideas and experiences; gaining knowledge and skills, and access to additional learning materials. Designing future programs to ensure a supportive and interactive learning community with attention cultural challenges may enhance learning from future Project ECHO programs.